Evaluation of the Paper and Smartphone Versions of the Quick Inventory of Depressive Symptomatology-Self-Report (QIDS-SR16) and the Patient Health Questionnaire-9 (PHQ-9) in Depressed Patients in China - Zhen L (Dove Medical Press, 2020)
Long Zhen,1,2 Gang Wang,1 Gailing Xu,2 Le Xiao,1 Lei Feng,1 Xu Chen,1 Man Liu,1 Xuequan Zhu1 1The National Clinical Research Center for Mental Disorders and Beijing Key Laboratory of Mental Disorders and Beijing Anding Hospital, Capital Medical University, Beijing 100088, People’s Republic of China; 2Tianjin Mental Health Center, Tianjin Anding Hospital, Tianjin 300222, People’s Republic of ChinaCorrespondence: Gang WangThe National Clinical Research Center for Mental Disorders & Beijing Key Laboratory of Mental Disorders & Beijing Anding Hospital, Capital Medical University, Beijing 100088, People’s Republic of ChinaTel +86-13672146258Fax +86-02288188856Email andingyjs@163.comPurpose: Smartphone-based questionnaires have advantages compared with their paper versions, but there is a lack of consistent research on depressive disorder questionnaires. This study aimed to assess the equivalence between the paper and smartphone versions of the Quick Inventory of Depressive Symptomatology-Self-Report (QIDS-SR16) and Patient Health Questionnaire-9 (PHQ-9) for patients with depressive disorders in psychiatric hospitals in China.Patients and Methods: This was a randomized crossover study of 110 depressed patients recruited from the outpatient department of Beijing Anding Hospital from March 2016 to September 2018. Group 1 completed both the QIDS-SR16 and PHQ-9 in paper format and then completed the smartphone version 1– 2 h later. Group 2 completed the scales in the reverse order. Reliability was evaluated using intraclass correlation coefficients (ICCs) with 95% confidence intervals (CI). The expected ICC was 0.9 (α=0.05).Results: The overall ICC score of the QIDS-SR16 paper and smartphone versions was 0.904 (95% CI: 0.861– 0.934), and the ICCs of each item ranged from 0.769 to 0.923. The overall ICC score of the PHQ-9 paper and smartphone versions was 0.951 (95% CI: 0.929– 0.967), and the ICCs of each item ranged from 0.779 to 0.914.Conclusion: This study demonstrated the equivalence of the paper and smartphone versions of the PHQ-9 and QIDS-SR16 in depressed patients in China.Keywords: depressive disorder, equivalence, intraclass correlation coefficient, questionnaires, smartphone